Cu-electrodeposited gold electrode for the sensitive electrokinetic investigations of nitrate reduction and detection of the nitrate ion in acidic medium - Abrar Yasir Abir; S.M. Nizam Uddin; Mahmudul Hasan; Md. Abdul Aziz; Shaheen Shah; Jahir Ahmed; Mohammad Abul Hasnat (Results in Chemistry, 2023)
The electro-catalytic reduction of nitrate ion in acidic media was observed at the Cu-electrodeposited Au surface. The voltammetric analysis represented that the Cu/Au electrode has an enhanced catalytic activity towards nitrate reduction in acidic medium through by eight electrons transfer process. Ammonia (NH3) was produced from the reduction of nitrate (NO3–) which followed a concerted reaction pathway as the value of transfer coefficient was 0.45 at Cu/Au electrode in the acidic medium. The value of standard rate constant and open circuit potential was evaluated as 2.48 × 10−4 cms−1 and 0.10 V respectively. This Cu/Au electrode displayed a good sensitivity (5.9378 μAµM−1cm−2) and lower detection limit (LOD: 0.52 µM) towards the reduction of nitrate ion and exhibited excellent performance in real sample analysis.